Differences in adhesion and biofilm formation among Candida albicans and Candida dubliniensis - Henriques, Mariana (2004)
Candida dubliniensis is an opportunistic yeast that can cause serious systemic diseases. This recently found yeast has been mismatched with Candida albicans once it presented similar genotypic and phenotypic characteristics. In the normal body flora, these yeasts exist predominantly in the form of biofilm. The main goal of this work was the evaluation of the ability for initial adhesion and biofilm formation by both Candida dubliniensis (two strains) and Candida albicans (one strain). To mimic the oral conditions the biofilms were formed on acrylic coupons in artificial saliva and using Sabouraud Dextrose Broth (SDB) as control medium. The biofilms were formed during 72 hours and compared in terms of total number of cells (using crystal violet) and activity (measured with XTT). In terms of initial adhesion, the three strains showed no statistical differences. However, the biofilm formed by Candida dubliniensis 7988 behaved similarly to the biofilm of Candida albicans, while the biofilm formed by Candida dubliniensis 7987 had a distinct evolution, either in SDB or saliva. The results show that Candida dubliniensis biofilm formation differs among strains and is not directly correlated with initial adhesion.